OPPORTUNITIES TO INCREASE EFFICIENCY THROUGH THE USE OF INNOVATIONS IN LIVESTOCK IN FARMS (American Journal of Business Management, Economics and Banking, 2023)
The article presents the possibilities of increasing productivity by applying innovations in livestock farming.